Pengaruh Tata Kelola Perusahaan, Leverage dan Return on Assets Terhadap Tax Avoidance - Iman Wahyudi; Sri Rustinawati (Sekolah Pascasarjana Perbanas Jakarta, 2020)
This study intends to test the influence of good corporate governance (GCG) by utilizing independent commissioners and the audit committee as proxies, leverage, and return on assets against tax avoidance. Population for the study is banking companies listed in the BEI from 2015 – 2017. By using purposive sampling method, 29 banking companies were selected as samples of the study. All the data used are secondary data which have been already published. The results proved that only audit committee that affected the practice of tax avoidance while independence commissioners, leverage and return on assets did not have any impact on tax avoidance. Keywords: GCG, leverage, ROA, tax avoidance.